Case Report: Physiotherapy Management of Post Operative ACL Reconstruction in Football Players - Irianto, Irianto; Nurfadillah, Dian; Nadhifah, Naurah (Ikatan Fisioterapi Indonesia cabang kota bekasi, 2024)
After Anterior Cruciate Ligament Reconstruction (ACLR), it is important to follow rehabilitation and postoperative instructions to facilitate recovery and avoid injury to the new graft tissue. Emphasis is placed on initial physical therapy and home exercises. Anterior Cruciate Ligament (ACL) injuries most commonly occur in sports activities that involve sudden stops or changes of direction, jumps and landings such as soccer. Purpose: to provide an overview of physiotherapy management in cases of ACL reconstruction. Methods: this study is a case report. Primary data obtained through autoanamnesis and physical examination. Results: 22 years old male patient complaints of swelling, muscle weakness, muscle atrophy and ROM limitation. Patients received physiotherapy interventions in 3 sessions per week for 2 weeks, with total 5 meetings. Results showed that it could reducing swelling and increasing Range of Motion (ROM). Conclusion: this case report describes the clinical presentation and physiotherapeutic management of ACL reconstruction. The physiotherapy program must be individualized taking into account the severity and clinical presentation of the patient.